Dos especies nuevas de Irenium (Cnidaria, Hydrozoa, Leptomedusae) en una bahía del Caribe Mexicano - Zamponi, M. O.; Suárez-Morales, E.; Gasca, R. (Revista de Biología Tropical, 1999)
Zooplankton samples collected al Bahía de la Ascensión, an embayment on the east coast of the Yucatan Peninsula, Mexico, yielded several specimens of leplomedusae which were assigned to the litlle-known genus Irenium Haeckel, 1879. This genus comprised only two species, I. quadrigatum Haeckel, 1879 and I. teuscheri (Haeckel, 1879), and has not been recorded after its original description almost 120 years ago. The taxonomical analysis of this material allowed the identification of two previously unknown species (I. labiatum and I. alabiatum) of this genus both of which are described herein. Both spccies have lateral spiral cini between tentacles and marginal warts; one of them (I. labiatum) has oral lips and the other has 110 lips (I. alabiatum). These features seem to be enough evidence to separate both specics between them and as previously undescribed. The new species have both a tropical distribution similar to that shown by the other Irenium species, suggesting a tropical origin for this genus, with a distribution pattern limited to neritic zones. This is the first record of the genus in the Northwestern Atlantic, and its occurrencc in the Caribhean Sea represents a relevant latitudinal range extension in the Western Hemisphere.